Neurological Manifestations in Primary Sjögren’s Syndrome: A Comparative Review of Inflammatory Mechanisms: Neuroinflammatory Mechanisms in Sjögren’s Syndrome - Moradi, Fatemeh; Shafiei, Golnaz; Shahrzad, Maryam; Mokhtari, Tahmineh (Journal of Contemporary Medical Sciences, 2025)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disorder marked by chronic inflammation, with neurological involvement often overlooked. This review highlights the inflammation-driven mechanisms underlying both peripheral and central nervous system (PNS, CNS) manifestations of pSS. PNS complications, particularly axonal sensorimotor and pure sensory neuropathies, are more common than CNS involvement. CNS abnormalities include diffuse white matter lesions and hippocampal atrophy. Immune dysregulation plays a central role, with emerging evidence implicating NLRP3 inflammasome activation and vasculitic processes. Aberrant B-cell activity may lead to pathogenic autoantibody production and direct neural injury. Infiltration of T- and B-cells into neural tissues, facilitated by astrocyte-mediated disruption of the blood-brain barrier, promotes cytokine-driven neuroinflammation. These processes contribute to cognitive, sensory, and motor dysfunction in pSS. Although conventional and biological therapies show promise, robust clinical trials are lacking. Understanding the immunopathogenesis of pSS may pave the way for targeted interventions. This review synthesizes current findings on neuroinflammatory mechanisms in pSS and their clinical implications.